Early Stage of Acute Coenurosis in Iranian Native Sheep- Case Report - Rahim Hobbenaghi; Mousa Tavassoli; Ali Nazarizadeh (Iranian Journal of Parasitology, 2014)
Cerebral coenurosis is the intermediary larval stage of Taenia multiceps, which affects intermediate hosts, particularly sheep and goats. In this report, gross and microscopic features of three scarce natural coenurosis cases, a oneyear-old ram and two lambs of 7 month old from a flock are explained. Atnecropsy, numerous small cysts measuring 5 to 10 mm in diameter were observed on both cerebrum and cerebellum surfaces, likewise multiple deep parts of which. In histopathological examination of the neural tissue, severe tissue destruction, a distinct layer of Gitter cells formation around the cysts,neuronophagia, gliosis and perivascular infiltration of lymphocytes were observed. In this early stage of parasite life cycle, larval migration and destruction of tissue, also aggregation of glial cells around the cysts cause a loose connection between cysts and neural tissue.